Controle estrutural do neógeno e quaternário nas bacias de campos e do espírito santo - Vincentelli, Maria Gabriela Castillo [UNESP]; Neves, Mirna; Morales, Norberto [UNESP] (My University, 2016)
The main oil production from Campos and Espírito Santo Basins is associated with Cenozoic turbidite reservoirs, most of them related to Oligo-Miocene age. The developed seismic interpretations show mix structures (structural-stratigraphic) with the main structural component at Neogene and Quaternary. The objective of this work is the main tectonic structures identification, characterization and interpretation, formed along the Neogene and Quaternary at the offshore region in these basins, using seismic interpretation integrated with potential method. The idea is to characterize the importance of the tectonic deformation, during this period, on the processes that define the reservoir, as well as the possible provinces definition that would contain specific exploratory plays. The analyses were done based on the geophysics data interpretation (seismic, wells and potential method) controlled by the Middle Miocene reflector and its deformation. As result, seven hidrocarbon´s provinces were identified, all of them limited mainly by fault systems with lateral projection of the outcropped basement and by neotectonics faults reactivated by ancient geological structures.
Structural control at Neogene and Quaternary in the Campos and Espírito Santo Basins